2012
DOI: 10.4236/ce.2012.38204
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Motivation for Learning among Minority Students: A Comparison between Students of Pre-Academic and Regular Programs

Abstract: Motivation for learning, which explains the impulses and motives for an individual to act to achieve his or her goals, is of great importance for students, particularly students of pre-academic preparatory programs. The literature suggests a relationship between self-esteem and motivation, yet there is a lack of studies that consider self-esteem among students in pre-academic preparatory programs and its relationship to motivation for learning. The main question of this study is whether there are differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 34 publications
2
15
0
2
Order By: Relevance
“…Similarly, Kussainov, Boulatbayeva and Shaumen (2014) found that there is no significant effect on students progression on academics in school because of the quality of education and developed knowledge. Zoabi (2012) said that the self-esteem has no significant correlation with motivation for learning of students in preparatory program. Osuafor and Okonkwo (2013) found that family background, family structure, parental occupation and parental education has no significant has no significant impact on student achievement in school.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Kussainov, Boulatbayeva and Shaumen (2014) found that there is no significant effect on students progression on academics in school because of the quality of education and developed knowledge. Zoabi (2012) said that the self-esteem has no significant correlation with motivation for learning of students in preparatory program. Osuafor and Okonkwo (2013) found that family background, family structure, parental occupation and parental education has no significant has no significant impact on student achievement in school.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Nematollahi, Tavakoli and Akbazzadeh (2017) said that self-esteem and academic achievement can be structured as good or bad because of daily task. Zoabi (2012) found that students who are prepare in their studies are more motivated same as regular students. In the Table 3 shows that the overall calculated weighted mean of the broken family and level of self-motivation has 3.37 out of 12 indicators and interpreted as sometimes.…”
Section: Instrumentmentioning
confidence: 96%
See 1 more Smart Citation
“…Teachers are responsible for providing the materials for the student that could measure their self-motivation in doing a specific task (Roshandel, Ghanizadeh, & Ghonsooly, 2018). Being unprepared for the future will decrease the students' motivation (Zoabi, 2012). However, both male and female students desire to succeed but they must put effort and perseverance in pursuing their dreams (Ojewola & Faremi, 2018).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In order to assess students' understanding in four main topics of digital Logic (State and sequential circuits, Number representations, MSI components, and Boolean Logic), we used questions from the Digital Logic Concept Inventory (DLCI) (Herman, 2011;Herman & Handzik, 2010;Herman, Kaczmarcczk, Loui, & Zilles, 2008, 2012Herman, Loui & Zilles, 2009, 2014Herman, Zilles & Loui, 2011). A concept inventory (CI) is a standardized assessment tool designed to measure stu-dents' understanding of the core concepts of a topic (Goldman et al, 2010), i.e., the extent to which it matches the accepted conceptual framework of a discipline.…”
Section: The Testmentioning
confidence: 99%